Auditoria forense como método de prevención de fraude en la Cooperativa de Ahorro y Crédito “San José” Ltda. Agencia Guaranda año 2024 - Sánchez Duran, Paulina Gabriela (2025)
This study applied a forensic audit to the "San José" Ltda. Savings and Credit Cooperative, Guaranda branch, for the 2024 period, aiming to prevent and identify fraud risks. Using a mixed-methods approach, financial statements were analyzed, and 25 employees were surveyed under the COSO I framework to evaluate internal control. The quantitative results did not reveal accounting fraud but showed critical vulnerabilities: an increase in the gross delinquency rate to 9.87%, a notable drop in profitability (ROE 0.87%) , and operational costs that exceed the financial margin. The qualitative analysis indicated a high level of ethical awareness among staff, but also weaknesses in the application of controls due to pressure to meet business goals and poor follow-up on audit findings. The study concludes that while the cooperative is robust in its documented structure, it faces significant operational risks. A plan is proposed to strengthen credit risk management, optimize efficiency, and consolidate an anti-fraud culture to mitigate the detected weaknesses